Diagnóstico socioeconómico de los pequeños comerciantes de la calle 9 de Octubre del cantón Pedro Carbo - Macias Pozo, Yhia Isabela (2024)
The objective of this research was to analyze the socio-economic situation of small traders in the main street 9 de Octubre in the canton of Pedro Carbo. The research used a mixed approach and descriptive methodology, combining both surveys and interviews. A survey was applied to a non-probabilistic sample of 38 business owners. The type of sampling was convenience sampling based on the willingness of the owners to participate in the study. The research revealed important findings and areas for improvement that could benefit small traders in the study area. The main results indicated that the economic dimension was assessed as fair, highlighting the gradual decline in sales revenue, high operating costs, mainly for basic services. The social dimension was assessed as good. However, the social dimension points to dissatisfactions related to security, social participation and support networks. Based on these results, a SWOT analysis was developed that led to concrete actions to improve the management of small traders in the study area, including: implementing digitization to compete with other traders through online sales and exclusive promotions, developing advertising strategies in alliance with local government to improve the visibility of the offer, among others.